Factors influencing the adoption of telemedicine for treatment of military veterans with post-traumatic stress disorder - Clemens Scott Kruse; James M. Atkins; Tiffany D. Baker; Estefania N. Gonzales; Jennifer L. Paul; Matthew Brooks (Medical Journals Sweden, 2018)
Background: Military veterans returning from a combat zone often face mental health challenges as a result of traumatic experiences. The veteran in the United States has been underdiagnosed and underserved. Since its advancement in the 1990s, telemedicine has become a more prevalent means of delivering services for post-traumatic stress disorder among veterans in the United States, but its adoption is not ubiquitous. Objective: To clarify the association of telemedicine and the treatment of veterans with post-traumatic stress disorder through identification of facilitators and barriers to the adoption of the modality. Methods: Reviewers analysed articles from CINAHL and PubMed databases, using relative key words, selecting the 28 most germane to the study objective. Results: The most common adoption facilitators were: improving access to rural populations of veterans (22%), effective treatment outcomes (16%), and decreased costs related to care (13%). The most prevalent barriers were: veterans lacking access to necessary modalities (25%), availability of physicians competent in post-traumatic stress disorder treatment (20%), and complications with technology (20%). Five themes surfaced for facilitators: accessibility, effectiveness, cost reduction, positive patient perception, and supportive community; and 5 themes for barriers: access to technology, technical complications, physician availability, negative patient perception, and uninformed patients. Conclusion: This literature review identifies cost and outcomes-effectiveness. The association of telemedicine with the treatment of veterans with post-traumatic stress disorder is feasible, beneficial and effective.